Triggering G‐Quadruplex Conformation Switching with [7]Helicenes. Issue 19 (5th March 2021) - Lousen, Bodil; Pedersen, Stephan K.; Răsădean, Dora M.; Pantoş, G. Dan; Pittelkow, Michael
Abstract: The dynamic interplay between two types of chiral structures; fully conjugated racemic hetero[7]helicenes and DNA strands prone to fold into G‐quadruplex structures is described. Both the [7]helicenes and the G‐quadruplex DNA structures exist in more than one conformation in solution. We show that the structures interact with and stabilise each other, mutually amplifying and stabilising certain conformations at increased temperatures. The [7]helicene ligands L1 and L2 stabilise the parallel conformation of k‐ras significantly, whereas hybrid (K + ) and antiparallel (Na + ) h‐telo G‐quadruplexes are stabilised upon conformational switching into altered G‐quadruplex conformations. Both L1 and L2 induce parallel G‐quadruplexes from hybrid structures (K + ) and L1 induces hybrid G‐quadruplexes from antiparallel conformations (Na + ). Enantioselective binding of one helicene enantiomer is observed for helicene ligand L2, and VTCD melting experiments are used to estimate the racemisation barrier of the helicene. Abstract : Stabilized by flexibility : Heterocyclic [7]helicenes and DNA strands prone to fold into G‐quadruplex structures interact with and stabilise each other, mutually amplifying and stabilising certain conformations at increased temperatures. The [7]helicene ligands stabilise the parallel conformation of k‐ras significantly, whereas hybrid (K + ) and antiparallel (Na + ) h‐telo G‐quadruplexes are stabilised upon conformational switching into altered G‐quadruplex conformations.